a. n-(n - 1) = 1
b. n( n - 1) = n² - n
c. (n - 1) + n = 2n - 1
d. (n - 1) + n = 2n - 1
<h3>Solution:</h3>
General Rule for Equation Solving
- Remove parentheses and combine like terms to simplify each side of the equation.
- To isolate the variable term on one side of the equation, use addition or subtraction.
- To find the variable, use multiplication or division.
Given two consecutive numbers , (n - 1) , n
simplifying :
n - (n - 1)
= n -1(n - 1)
= n - n + 1
= 1
multiplying :
n( n -1)
= n² - n
simplifying :
(n-1) + n
= n - 1 + n
= 2n -1
by adding two numbers :
(n - 1) + n
= n -1 + n
= 2n - 1
To learn more about equations refer to :
brainly.com/question/22688504
#SPJ13
Answer:
Part 1)
Part 2)
Step-by-step explanation:
Part 1) Find the value of x
we know that
Triangles CDF and FDE are similar
therefore
The ratio of its corresponding sides is proportional and its corresponding angles are congruent
so
Part 2) Find the length of DE
substitute the value of x
The z-score tells you how many standard deviations from the mean.
<span>1.5 * 3.6 = 5.4 miles </span>
<span>So anything within 5.4 miles of the average (29). </span>
<span>The range would be: </span>
<span>29 - 5.4 = 23.6 </span>
<span>to: </span>
<span>29 + 5.4 = 34.4 </span>
<span>23.6 ≤ x ≤ 34.4 </span>
<span>Answer: </span>
<span>B) 24 miles</span>
Answer:
3x-y=12
3x-12=y
to find value of
8x/2y
8x/2(3x-12)
8x/6x-24
8x/6x-8x/24
4/3-x/3
4-x/3
Step-by-step explanation:
Step-by-step explanation:
log (√1000000x)
Rewrite √1000000x as (1000000x)1/2.
expand long ((1000000x)1/2) by moving 1/2
oby moving logarithm.
1/2 longth (1000000x)
Rewrite
log
(1000000x) as log(1000000)+log(x).
1/2(log(1000000)+log(x))
Logarithm base 10 of 1000000 is 6.
1/2(6+log(x))
Apply the distributive property.
1/2.6+1/2 log(x)
Cancel the common factor of 2.
3+1/2 long(x)
Combine 1/2 and log(x)
3+ long(x)/2